Determinants of exchange rate in Ghana: Cointegration and wavelet analysis. - Abavare, Eric K. K. (KNUST, 2025)
A Thesis Submitted To The School Of Graduate Studies In Partial Fulfilment Of The Requirements For The Award Of Master Of Philosophy In Finance.